Porto-mesenteric vein thrombosis following laparoscopic sleeve gastrectomy for morbid obesity: Case series and literature review. (2019) - Alenazi, Naif A.; Ahmad, Khaled S.; Essa, Mohamed S.; Alrushdan, Mahir S.; Al-Shoaibi, Abdulbaset M.
Highlights: Porto-mesenteric vein thrombosis is rare and fatal complication after laparoscopic sleeve gastrectomy (LSG) for morbidly obese patients. Most patients presented with vague abdominal symptoms, so the physician should has high index of suspicion to recommend CT abdomen. Early diagnosis is of paramount importance for better outcome. Prophylactic anticoagulant is essential after LSG to prevent PMVT. Abstract: Background: Portal vein thrombosis is a rare and a potentially lethal complication of Laparoscopic sleeve gastrectomy. In this series, we describe the presentation, treatment, and outcome of 5 cases of PMVT post-laparoscopic sleeve gastrectomy (LSG) treated successfully at our hospital. Case report: Five patients presented to our emergency department with diffuse abdominal pain associated with anorexia, nausea and vomiting after laparoscopic sleeve gastrectomy (LSG). Computed tomography (CT) scan showed evidence of portal, mesenteric and splenic vein thrombosis and small bowel ischemia in three patients. Two patients were treated only with anticoagulant and the other three patients were treated with surgery in the form of diagnostic laparoscopy converted to laparotomy with Small bowel resection. Conclusion: Portal and mesenteric venous thrombosis after laparoscopic sleeve gastrectomy is an unusual complication but it has life threatening consequences if it is not diagnosed early and treated adequately. The patients with porto-mesenteric venous thrombosis (PMVT) usually present themselves with vague abdominal symptoms. As so, the physicians should have high index of suspicion to recommend computed tomography (CT) abdomen to confirm diagnosis and start adequate treatment.